The breadwinner - Ellis, Deborah, 1960- (Berkeley, CA : Distributed in the U.S.A. by Publishers Group West, 2006)
Because the Taliban rulers of Kabul, Afghanistan, impose strict limitations on women's freedom and behavior, eleven-year-old Parvana must disguise herself as a boy so that her family can survive after her father's arrest.
"Groundwood Books.".
Book Links (A.L.A.).
Five Owls.
Publisher's Weekly.
6.0
6.1.
Keywords: Family life -- Fiction; Friendship -- Fiction; Sex role -- Afghanistan -- Fiction; Women -- Employment -- Fiction; Family life -- Fiction; Friendship -- Fiction; Sex role -- Fiction; Women -- Employment -- Fiction; Afghanistan -- Fiction; Afghanistan -- Fiction